2017
DOI: 10.1002/adom.201700243
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Spring‐Like Shell Templated from Cholesteric Liquid Crystal Prepared by Microfluidics

Abstract: Solid‐state photonic shells are prepared with a reactive cholesteric liquid crystal (CLC) mixture that consists of a reactive mesogen mixture and the nonreactive chiral dopant. The shells are prepared using a microfluidic glass‐capillary chip, followed by UV‐curing and extraction of the chiral dopant. CLC shells with relatively uniform thickness are produced by density matching and annealing. The produced solid‐state CLC (CLCsolid) shells show a good reversible swelling/shrinkage behavior that is dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…Yet, the delicate nature of the liquid–liquid interfaces bounding regular LC shells represents a drawback, limiting their lifetime and preventing their removal from the continuous liquid phase. To circumvent this limitation, some reports have included mesogens with polymerizable end groups, either for polymer stabilization of a shell that remains largely fluid or for turning the shell into a polymeric solid or rubber . So far, only one study was presented with LCN shell actuators .…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the delicate nature of the liquid–liquid interfaces bounding regular LC shells represents a drawback, limiting their lifetime and preventing their removal from the continuous liquid phase. To circumvent this limitation, some reports have included mesogens with polymerizable end groups, either for polymer stabilization of a shell that remains largely fluid or for turning the shell into a polymeric solid or rubber . So far, only one study was presented with LCN shell actuators .…”
Section: Introductionmentioning
confidence: 99%
“…Past decades are characterized by the explosive development of technologies based on optoelectronics and photonics . The modern elemental base of these technologies includes refractive, diffraction and optical fiber components.…”
Section: Introductionmentioning
confidence: 99%
“…The employ of photoresponsive molecular switches enabled a wide tuning range of the pitch length of CLCs and hence of the highly selective CP reflection wavelength emanating from paired spherical CLC Bragg reflectors [ 16 ]. In addition, it was reported that the transition from droplets to shells gave rise to sharp patterns and sustained excellent optical quality even after polymerization [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is difficult to manipulate each individual spherical CLC Bragg reflector and organize relatively small amounts of them into various separated geometric figures independently. Very recently, by means of magnetic manipulation strategies, the noncontact transport of CLC microshells was successfully achieved with microfluidic devices [ 13 , 19 ]. Chen et al fabricated dye-doped CLC microshells encapsulated with water-dispersible Fe 3 O 4 nanoparticles for a magnetically-transportable tunable microlaser [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation